Peningkatan Hasil Belajar IPA Dengan Penerapan Model Problem Based Instruction Siswa Kelas IV SDN 004 Bangkinang Kota - Edo Rinaldi; Melvi Lesmana (Jurnal Pendidikan Tuntas, 2023)
This researd is based on the results of student on science subject grade IV SDN 004 Bangkinang City. One of the solution to solve this problem is to apply Problem Based Instruction model. The purpose of this researd is to describe the Improving of Science learning subject on topic environment changes by applying Problem Based Instruction Model at 4 grade students of SDN 004 Bangkinang city. The method of this research is Classroom Action Research (CAR) implemented in two cycles and each cycle held two meetings. Each cycle consists of two meetings and four phases, are planning, implementating, observating, reflecting, and schedule of this research begun from April until May 2017. The subjects thery are of this researd is student grade 4 of SDN 004 Bangkinang city. which 16 students, the are 10 male students, and 6 female students. of colection the techniques of used in this researd are observation, documentation, and test. Based on the results of learning is can be concluded that the first cycle is still quite average with an average of 74, then from 16 students only 12 students or 75% who achieve mastery individually. The result of Student learning in cycle II is good with an average of 86.60, and 14 students complete or 87.5% who achieve mastery individually. Thus it can be concluded that with the applications of Problem Based Instruction Model can improve the results of learning environmental changes at 4 grade students SDN 004 Bangkinang City